The Courts' Approach to Sentencing for Adultery Offences and its Implication on Women and Children: A Case Study in Sudan: (Pendekatan Mahkamah Menjatuhkan Hukuman terhadap Kesalahan Zina dan Implikasinya kepada Wanita dan Kanak-kanak: Kajian Kes di Sudan) (Kanun: Jurnal Undang-undang Malaysia, 2016)
This article discusses adultery and rape cases in Sudan. Adultery is proven through a woman's pregnancy without the need for further proof, putting the woman in a situation that can be considered unjust, as she is considered to have committed adultery even when she could have been the victim of rape. Furthermore, rape is categorized as a form of adultery, and the courts' approach is the same, i.e. there is a requirement to bring four witnesses. As a result, rapists usually escape punishment. The suggestion is that rape should be categorized as a ta'zir offence, while the requirement for four witnesses should be done away with, while DNA evidence, witness testimony and medical reports should be made admissible to enable the punishment of rapists in a manner that will requite the suffering of the victims.Keywords: court, Islamic criminal law, rape, adultery